Dupuytren's contracture: an analysis of outcomes of percutaneous needle fasciotomy versus open fasciectomy. Issue 9 (20th January 2014) - Toppi, Jason T.; Trompf, Leisel; Smoll, Nicolas R.; Lim, Vivian; Smith, Katrina; Findlay, Michael W.; Hunter‐Smith, David J.
Abstract Background Percutaneous needle fasciotomy (PNF) is a minimally invasive technique used to manage Dupuytren's contracture. We compared outcomes of PNF versus open fasciectomy (OF) to examine the suitability of PNF in Australia. Method A retrospective cohort study using two questionnaires regarding Dupuytren's treatment was used to assess patients with uncomplicated primary disease. The primary outcomes were immediate and medium‐term correction of contracture (2‐year mean follow‐up to time of survey). Secondary outcomes were patient satisfaction and complications including tendon/nerve injury, infection, skin necrosis and vascular damage. Results One hundred fifty‐five out of 191 surveys were returned (81%). The final analysis included 125 cases (65%), 73 PNF and 52 OF. No significant differences were observed between both groups with regards to follow‐up time, gender, smoking status, co‐morbidities or preoperative deformity grade. No significant differences were observed in terms of immediate or medium‐term deformity correction, tendon/nerve injury or circulatory complications. The postoperative infection rate was higher with OF, with these patients 7.57 (95% confidence interval 1.56, 36.77; P = 0.01) times as likely to have a postoperative infection as patients undergoing PNF. A higher number of patients who underwent PNF were told that they would require another operation (30% versus 12%; P = 0.02). Satisfaction scores were similar (OF 33.2 versus PNF 32.6; P = 0.82). Conclusion The OF and PNF procedures provide comparable deformity correction for uncomplicated primary Dupuytren's disease in the immediate perioperative period. The reduced side effect profile of PNF should prompt surgeons to consider incorporating it in their practice for the first‐line management of uncomplicated primary Dupuytren's disease.